2018
DOI: 10.1002/sce.21457
|View full text |Cite
|
Sign up to set email alerts
|

Students’ representational competence with drawing technology across two domains of science

Abstract: Research has indicated the importance of representational competence for learning science. Issues related to the nature of students’ representational competence, such as how they demonstrate representational competence across different domains of science, require investigation. In the present study, four aspects of representational competence across two domains of science were investigated: use of dynamic representations, use of multiple representations, use of adequate science concepts, and use of visualizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
0
20
3
1
Order By: Relevance
“…Studies on the efficacy of drawing for improving STEM learning outcomes have demonstrated the independent utility of drawing for improving learning (e.g., Cromley et al (2020) for a review). With the appropriate scaffolds, drawing has been demonstrated to support students' developing mental models of scientific phenomena presented primarily through text-based instructional materials (e.g., Chang, 2018;Gobert, 2005;Schleinschock, Eitel, & Scheiter, 2017); Schwamborn et al, 2011) and animations (e.g., Wu & Rau, 2018). These studies suggest that activities focused on drawing disciplinary representations may better help students to develop the skills associated with RC in a domain that will, in turn, facilitate their learning of disciplinary concepts related to various scientific models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the efficacy of drawing for improving STEM learning outcomes have demonstrated the independent utility of drawing for improving learning (e.g., Cromley et al (2020) for a review). With the appropriate scaffolds, drawing has been demonstrated to support students' developing mental models of scientific phenomena presented primarily through text-based instructional materials (e.g., Chang, 2018;Gobert, 2005;Schleinschock, Eitel, & Scheiter, 2017); Schwamborn et al, 2011) and animations (e.g., Wu & Rau, 2018). These studies suggest that activities focused on drawing disciplinary representations may better help students to develop the skills associated with RC in a domain that will, in turn, facilitate their learning of disciplinary concepts related to various scientific models.…”
Section: Discussionmentioning
confidence: 99%
“…Students' ability to understand images, and understand the relationship between variables in the picture affected learning outcomes. Students with good image representation ability, has a good learning outcome, because the representation serves as a tool to help solve problems in physics [26] [12] and make it easier to understand and explain certain phenomena [10][27] [28].…”
Section: Results and Analysismentioning
confidence: 99%
“…Recent studies have also examined analyzing students' representational competence using drawing technology across different topics (H. Y. Chang, 2018) as well as developing analytical frameworks to understand the various meanings made in student-generated drawings (Tang et al, 2019).…”
Section: Student-generated Drawings As Science Learningmentioning
confidence: 99%